2021
DOI: 10.1093/bib/bbab144
|View full text |Cite
|
Sign up to set email alerts
|

Comparative phylogenetic analysis of SARS-CoV-2 spike protein—possibility effect on virus spillover

Abstract: Coronavirus disease 2019 has developed into a dramatic pandemic with tremendous global impact. The receptor-binding motif (RBM) region of the causative virus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), binds to host angiotensin-converting enzyme 2 (ACE2) receptors for infection. As ACE2 receptors are highly conserved within vertebrate species, SARS-CoV-2 can infect significant animal species as well as human populations. An analysis of SARS-CoV-2 genotypes isolated from human and significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
(33 reference statements)
0
7
0
1
Order By: Relevance
“…The Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) the causal agent of a zoonotic disease called COVID-19 infected more than 422 M people including 5.8 M deaths as of February 2022 [ 1 , 2 ]. Despite the widespread vaccination against the disease, the global number of new cases increased sharply due to the attenuation of the vaccine-induced immunity over time and the emergence of new variants [ 1 , [3] , [4] , [5] ].…”
Section: Introductionmentioning
confidence: 99%
“…The Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) the causal agent of a zoonotic disease called COVID-19 infected more than 422 M people including 5.8 M deaths as of February 2022 [ 1 , 2 ]. Despite the widespread vaccination against the disease, the global number of new cases increased sharply due to the attenuation of the vaccine-induced immunity over time and the emergence of new variants [ 1 , [3] , [4] , [5] ].…”
Section: Introductionmentioning
confidence: 99%
“…Gamma parameter for site rates was calculated and our data showed that gamma parameter for S protein is higher than the whole-viral genome; thus more positive selective pressure is on S protein and this may be related to selection pressure exerted by the adaptive immune response ( Table 3 ) ( Gelman et al, 2020 ). SNPs of SARS-CoV-2 naturally exist in the population ( Ghorbani et al, 2020a ) or accumulate in a new variant when the virus circulates in different hosts ( Ghorbani et al, 2021 )but their frequency is related to positive selection by mAbs and vaccines ( Gelman et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Classi cation of SARS-CoV-2 Clades and Construction of the Phylogenetic Tree Phylogenic construction was made in Mega-X from previous alignment results, using the Neighbor-Joining (NJ) Bootstrap 1000 replication method (Gaffar et al 2021;Ghorbani et al 2021;Tabibzadeh et al 2020) from 18 random high coverage sequences from Indonesian representative for each type of GISAID clade, as well as Wuhan-Hu-1 as a reference. Then, the sequences were also analyzed for the type of PANGOLIN variant, as well as the status of the variant using the COG-UK web application (https://pangolin.cog-uk.io/) (O'Toole 2021; Rambaut et al 2020).…”
Section: Data Miningmentioning
confidence: 99%